The Photoshop Elements 2020 book for digital photographers - Kelby, Scott (Voices that matter., 2020)
ARE YOU READY FOR AN ELEMENTS BOOK THAT BREAKS ALL THE RULES? This book breaks new ground by doing something for digital photographers that's never been done before-it cuts through the bull and shows you exactly "how to do it." It's not a bunch of theory; it doesn't challenge you to come up with your own settings or figure things out on your own. Instead, it does something that virtually no other Elements book has ever done-it tells you flat-out which settings to use, when to use them, and why. If you're looking for one of those "tell-me-everything-about-the-Unsharp-Mask-filter" books, this isn't it. You can grab any other Elements book on the shelf, because they all do that. Instead, this book gives you the inside tips and tricks of the trade for organizing, correcting, editing, sharpening, retouching, and printing your photos like a pro. You'll be absolutely amazed at how easy and effective these techniques are-once you know the secrets. LEARN HOW THE PROS DO IT Each year Scott trains thousands of digital photographers and, almost without exception, they have the same questions and face the same problems-that's exactly what he covers in this book. You'll learn: How to unlock the power of layers (you'll be amazed at how easy it is!) How to use Camera Raw for processing not only RAW photos, but JPEGs, TIFFs, and PSDs too! (And you'll learn why so many pros like it best-because it's faster and easier) The sharpening techniques the pros really use (there's an entire chapter just on this!) How to deal with common digital camera image problems, including brightening people in dark shadows and getting the best color possible The most requested photographic special effects, and much more! THE BOOK'S SECRET WEAPON Although Elements 2020 offers some digital photography features that Photoshop doesn't offer, there are plenty of features that Photoshop has that Elements 2020 doesn't (like channels, HDR, etc.). But in this book, you'll learn some slick workarounds, cheats, and fairly ingenious ways to replicate many of those Photoshop features right within Elements. Plus, you can download many of the images used in the book, so you can follow right along with the techniques. Since this book is designed for photographers, it doesn't waste your time talking about what a pixel is, how to frame a shot or set your exposure, etc., and there's no talk about which camera or printer to buy. It's all Elements, step by step, cover to cover, in the only book o ...